REPATRIASI LUKISAN PITA MAHA DAN PENGUATAN HISTORIOGRAFI SENI RUPA MODERN BALI - Dewi, Citra Smara; Drijono, Sabila Duhita (UI Scholars Hub, 2026)
This article examines the repatriation of Pita Maha paintings from the 1930s to 1940s, which were returned by the Government of the Netherlands to Indonesia in 2024. Pita Maha, an artistic movement established in Ubud, Bali in 1936, holds an important position in art historiography as a key contributor to the development of modern Balinese painting. The repatriation of these works provides an opportunity to reconsider and expand existing historical narratives. Accordingly, this study aims to contribute to the enrichment of the historiography of modern Balinese painting. The research employs a historical method —encompassing heuristics, source criticism, interpretation, and historiography— combined with visual analysis of a selected sample of five paintings. These works were chosen based on their thematic, ideological, and formal characteristics. The novelty of this study lies in its use of newly repatriated paintings as primary historical sources. The findings identify three recurring thematic dimensions: (1) traditional narratives and Balinese cosmology, (2) everyday life and social traces, and (3) historical and political symbolism. The presence of socio-political elements within these works suggests that Pita Maha artists engaged not only with spiritual and aesthetic concerns, but also with the social and political dynamics of their time, reflecting a broader spectrum of artistic concerns than has been emphasized in existing scholarship. This study highlights the potential of repatriation to contribute to more nuanced and expanded readings of modern Indonesian art historiography.